ChemInform Abstract: Photoluminescent Metal‐Organic Frameworks for Gas Sensing. Issue 44 (13th October 2016) - Lin, Rui‐Biao; Liu, Si‐Yang; Ye, Jia‐Wen; Li, Xu‐Yu; Zhang, Jie‐Peng
Abstract: Review: 148 refs.